1, 10-Phenanthroline ring-opening mediated by cis-{Re(CO)2} complexes. Issue 3 (12th December 2022) - Cañadas, Purificación; Pérez, Julio; López, Ramón; Riera, Lucía
Abstract : C–N bond cleavage of pyridine rings bonded to well-defined cis -dicarbonyl Re(i ) complexes has been achieved, affording bipy and phen (for the first time) ring-opening products. Abstract : Pyridine ring-opening of a metal-coordinated 1, 10-phenanthroline has been demonstrated for the first time. The reaction of stable, well-defined cis, trans -[Re(CO)2 (N–N)(N-RIm)(PMe3 )]OTf [N–N = 2, 2′-bipyridine (bipy), N-RIm = N -alkylimidazole] compounds with KN(SiMe3 )2 followed by the addition of an excess of electrophile (MeOTf) afforded bipy ring-opening products easily at room temperature. The new, electron rich analogous 1, 10-phenanthroline (phen) cis -{Re(CO)2 } complexes allowed also, under mild conditions, the ring-opening of phen, which can be regarded as a model of coordinated quinoline, one of the impurities in fuels most difficult to eliminate by the hydrodenitrogenation (HDN) process. The phenanthroline ring-opening products are regiochemically different from those obtained with bipy, and the results of computational calculations suggest that the difference can be traced to the avoidance of a larger loss of aromaticity. The new ring-opening products have been spectroscopically characterized in solution and by means of X-ray diffraction in the solid state.